I d'A : Initiatief d'Amis. - Van Mulders, Wim; Vooruit, vzw Socio-Cultureel Centrum, Gent (Gent : Vooruit, 1986)
Beyls, Peter ; Bervoets, Fred ; Bijl, Guillaume ; B.I.W.A. ; Castelyns, Frank F. ; Charlier, Jacques ; Cole, Willem ; Copers, Leo ; Daems, Walter ; Deleu, Luc ; Denmark ; De Vylder, Paul ; d'Oultremont, Juan ; Droste, Monika ; Duck, Colette ; Dutrieux, Daniel ; Fabre, Jan ; Francis, Filip ; François, Michel ; Geirlandt, Toni ; Goossens, Walter ; Grossen, Luc ; Huet, Wilfried ; Janssens, Ann Veronica ; kluyskens, Bernadette ; Lizene, Jacques ; Lohaus, Bernd ; Mees, Guy ; Mesmaeker, Jacqueline ; Navez, Jean-Marc ; Oosterlynck, Baudouin ; Pacquée, Ria ; Ransonnet, Jean-Pierre ; Roelandt, Hugo ; Rombouts, Guy ; Scarpulla, Russell ; Smits, George ; Somerlinck, Jef ; Van den Berghe, Frank ; Van Roosmaelen, Frans ; Van Snick, Philippe ; Vercammen, Wout ; Vergara Santiago, Angel ; Villers, Bernard ; Voordeckers, Jürgen
Engels
Frans
Nederlands
Nederlands & Frans & Engels
I d'A : Initiatief d'Amis, Vooruit Gent, VZW Socio-Cultureel Centrum Vooruit Gent, 21 juni - 7 september 1986
boek